(untitled) (Dhaka University Journal of Biological Sciences, 2012)
Purpose of the study was to explore the mental health problems in different functional areas of women who are undergoing divorce process. It was found that these women were suffering from various types of psychological problems. Symptoms found in different functional areas included ? physiological function impairments (e.g. weakness and tired, low appetite, sleep disturbance, headache, chest pain, brain stroke, senseless, numbness etc.), emotional function impairments (e.g. helplessness all the time, severely depressed, frustrated, anxious, upset, hopelessness, suicidal ideation, low confidence, low self?esteem, etc.), cognitive impairments (e.g. distressful thought about real life crisis ? ?I have become valueless?, ?I have no way?, ?I do not want to live anymore? etc.), behavioral impairments (e.g. unable to perform household chores, lose temper for every silly thing, misbehave with family members and relatives etc.), occupational function impairments (e.g. declined level of interest, unable to take any responsibility, dependent on others, etc.), social function impairments (e.g. avoided any social program, felt embarrassed to meet other people, isolated etc.), sexual function impairments (e.g. no interest in this area, no demand etc.). These findings suggest that women in divorce process have strong need for mental health support for rebuilding their mental health status. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11517 Dhaka Univ. J. Biol. Sci. 21(2): 191-196, 2012 (July)